Avaliacao da performance muscular em atletas profissionais de futebol de campo - Vidmar, M. F.; Dellagerisi, M.; Demarchi Kappel, M.; Pasqualotti, A.; Faria Silva, M.; Lopes Pimentel, G.; Almeida, C. R. (Revista Brasileira de Ciência e Movimento, 2013)
Nowadays, soccer is the most practiced sport in the world and the assessment of muscle strength has been used to improve the results and prevention of sports injuries. The purpose of this study was evaluate during the season the isokinetic performance of knee flexion and extension muscles in different positions of professional soccer players. This is an observational study using a transversal approach professional soccer players were submitted to isokinetic test (N= 24), using the concentric/concentric protocol for flexion and extension muscles of the knees at 60 and 300°/s for five repetitions each, with an interval of 30 seconds rest and visual and verbal feedback. The collected data evidenced higher peak torque at dominant limb flexor knee muscle when compared to non-dominant limb in midfield at 60°/s (p=0,04*) and 300°/s (p=0,02*). However, in the peak torque of knee extensor this significant difference for the dominant limb was found only in defenders in both at angular velocities (p=<0,00* for both). When performing the comparison between the different positions on the field, there was no significant difference in both the group muscle and angular velocities. The conventional reason bias range was between 48.5% and 59.2%. The findings of this study suggest that athletes prioritize the dominant limb during the trainings and games, feature a power deficit values within normality, but a conventional reason below that relates the literature, showing risk of developing muscle injury during the season.